Total shoulder arthroplasty does not correct the orientation of the eroded glenoid. - Gregory, Thomas; Hansen, Ulrich; Emery, Roger; Amis, Andrew A; Mutchler, Celine; Taillieu, Fabienne; Augereau, Bernard (Acta Orthopaedica, 2012)
Background and purpose Alignment of the glenoid component with the scapula during total shoulder arthroplasty (TSA) is challenging due to glenoid erosion and lack of both bone stock and guiding landmarks. We determined the extent to which the implant position is governed by the preoperative erosion of the glenoid. Also, we investigated whether excessive erosion of the glenoid is associated with perforation of the glenoid vault. Methods We used preoperative and postoperative CT scans of 29 TSAs to assess version, inclination, rotation, and offset of the glenoid relative to the scapula plane. The position of the implant keel within the glenoid vault was classified into three types: centrally positioned, component touching vault cortex, and perforation of the cortex. Results Preoperative glenoid erosion was statistically significantly linked to the postoperative placement of the implant regarding all position parameters. Retroversion of the eroded glenoid was on average 10° (SD10) and retroversion of the implant after surgery was 7° (SD11). The implant keel was centered within the vault in 7 of 29 patients and the glenoid vault was perforated in 5 patients. Anterior cortex perforation was most frequent and was associated with severe preoperative posterior erosion, causing implant retroversion. Interpretation The position of the glenoid component reflected the preoperative erosion and 'correction' was not a characteristic of the reconstructive surgery. Severe erosion appears to be linked to vault perforation. If malalignment and perforation are associated with loosening, our results suggest reorientation of the implant relative to the eroded surface.